Human Factor in Green Supply Chain - Mohamad, Mohd Fathi; M Udin, Zulkifli; Imran Sharif, Kamal (International Journal of Supply Chain Management, 2018)
Implementation of green supply chain is an important in leading a firm, organization or company to gaining competitive advantage. In this research study, the variables have influence towards the implementation of green supply chain are identified, they are human factor. Human factor that researcher have used in this study is safety and health, attitude, personal factor and workload which was used as independent variables in this study. Total of 105 sample size has been taken from third year student who taking International Business course as respondents. Study survey has been conducted through random sampling. A total 110 questionnaires have been distributed to the sample of chosen consists the four independent variables of human factor, that are safety and health, attitude, personal factor and workload, while green supply chain is the dependent variable. Quantitative survey had been used for this study. From regression analysis result showed all hypotheses supported with significant value. The result concludes that all the independent variable in this study give a significant impact to the implementation of green supply chain